The Influence Of Brand Equity On Consumer's Buying Behavior: A Malaysia Perspective - Seow, Yuan Shyong (2008)
The study examines the influence of brand equity on consumer's buying behavior. The data collection was based on the survey done via 200 questionnaires that was carried out through the internet with respondents from Klang Valley.